2020
DOI: 10.3390/diagnostics10020108
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Outcomes of Early Enzyme Replacement Therapy for Mucopolysaccharidosis IV: Clinical Case Studies of Two Siblings

Abstract: Enzyme replacement therapy (ERT) is one of the available therapies for mucopolysaccharidosis (MPS). This study presents a follow-up of two siblings with MPS IVA (Morquio A disease) that received ERT. Both siblings received weekly intravenous infusions of elosulfase alfa for 4.5 years. One sibling (patient 1, P1; male) started therapy at 54 months of age, and the other sibling (patient 2, P2; female) started at 11 months of age. ERT was well-tolerated. In comparison to P1, P2's growth curves deviated less from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Our growth data in the two infants are remarkable given the progressive deviation from normal growth curves after 2 years of age described for untreated patients with Morquio A syndrome [2,14,22]. These observations are particularly relevant considering the very limited data currently available for Morquio A patients starting ERT at this early age [22,24,25]. Our data confirm recent findings from a study of two siblings with Morquio A starting ERT at the ages of 54 months and 11 months.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our growth data in the two infants are remarkable given the progressive deviation from normal growth curves after 2 years of age described for untreated patients with Morquio A syndrome [2,14,22]. These observations are particularly relevant considering the very limited data currently available for Morquio A patients starting ERT at this early age [22,24,25]. Our data confirm recent findings from a study of two siblings with Morquio A starting ERT at the ages of 54 months and 11 months.…”
Section: Discussionsupporting
confidence: 88%
“…Our data confirm recent findings from a study of two siblings with Morquio A starting ERT at the ages of 54 months and 11 months. Over 4.5 years of treatment, growth of the youngest sibling deviated less from the norms than that of the older sibling, although a significant growth retardation was still seen after 2 years of age [24]. Other studies showed mixed results [22,25].…”
Section: Discussionmentioning
confidence: 93%
“…Earlier introduction of ERT in MPS patients may improve disease course in the long-term or prevent permanent damage (Muenzer, 2011). Although early diagnosis and initiation of ERT do not reverse orthopedic and musculoskeletal problems and developmental retardation, it can slow the rate of disease progression (Barak et al, 2020). In our study, ERT did not result in a difference in motor functions of the patients as assessed by 6MWT, TUG and functional reach tests and only functional independence level was higher in children receiving ERT.…”
Section: Discussionmentioning
confidence: 45%
“…Elosulfase alfa (Vimizim TM ) was introduced as the first medication approved by the US Food and Drug Administration (FDA) for the treatment of MPS IV in April 2014 (1,2,13,14) and by National Institute for Health and Care Excellence (NICE) in the UK in December 2015 (15). Elosulfase alfa is an enzyme replacement therapy (ERT) providing exogenous N-acetylgalactosamine-6-sulfatase, which improves the catabolism of C6S and KS (15).…”
Section: Introductionmentioning
confidence: 99%